Bromo-dragonfly, a psychoactive benzodifuran, is resistant to hepatic metabolism and potently inhibits monoamine oxidase A. (1st October 2018) - Noble, Carolina; Holm, Niels Bjerre; Mardal, Marie; Linnet, Kristian
Highlights: Slight structural differences between benzodifuran analogues lead to high differences in their hepatic metabolism and toxicity. Bromo-dragonfly is highly stable in hepatic fractions. Bromo-dragonfly strongly inhibits oxidative deamination of 5-HT by MAO-A. Abstract: Bromo-dragonfly is a benzodifuran derivative known as one of the most potent 5-HT2A -receptor agonists within this chemical class, with long-lasting effects of up to 2–3 days. In addition to hallucinogenic effects, the drug is a potent vasoconstrictor, resulting in severe adverse effects, such as necrosis of the limbs. In some cases, intoxication has had fatal outcomes. Little is known about the metabolism of bromo-dragonfly. The aims of this study were to investigate the pharmacokinetics of bromo-dragonfly, determine the plasma protein binding, examine the human hepatic metabolism in vitro, and compare with those of its close analogue, 2C-B-fly. Additionally, we assayed the inhibition potency of both compounds on the monoamine oxidase (MAO) A- and B-mediated oxidative deamination of serotonin (5-HT) and dopamine, respectively. Liquid chromatography high-resolution mass spectrometry was used for metabolism studies in pooled human liver microsomes (HLM), pooled human liver cytosol (HLC) and recombinant enzymes. Inhibition studies of the deamination of 5-HT and dopamine were carried out using LC–MS/MS. Bromo-dragonfly was not metabolised in the tested in vitro systems. On the other hand, 2C-B-fly was metabolised in HLM by CYP2D6 and in HLC to some extent, with the main biotransformations being monohydroxylation and N -acetylation. Furthermore, MAO-A metabolised 2C-B-fly, producing the aldehyde metabolite, which was trapped in vitro with methoxyamine. Inhibition experiments revealed that bromo-dragonfly is a competitive inhibitor of MAO-A with a Ki of 0.352 μM. The IC50 value for bromo-dragonfly indicated that the inhibition of MAO-A may be clinically relevant. However, more data are needed to estimate its impact on the increase of 5-HT in vivo .